Vitamin D Deficiency in Adults with Musculoskeletal Pain - Sevgi Gümüş Atalay; Roni Atalay; Berat Meryem Alkan; Fatma Fidan; Sinem Bozkurt; Hatice Aksekili; Özge Ardıçoğlu (Galenos Yayinevi, 2015)
Objective: The aim of this study was to determine whether vitamin D deficiency in patients with musculoskeletal pain who were admitted to our hospital and to establish the difference between vitamin D levels according to gender and age groups. Materials and Methods: Among 28.702 patients, 857 (3%) patients whose vitamin D levels were studied were included in the study. Serum 25(OH) D level was determined by liquid chromatography-mass spectrometry (LC-MS). The patients were divided into three groups according to 25(OH) D level as; Group 1: >30 μg/L (sufficient), group 2: 10-30 μg/L (moderate insufficient), and group 3: <10 μg/L (severe insufficient). Results: The mean age of the patients were 49.1±14.5 (18-87) years and the mean serum vitamin D levels of patients admitted to our hospital were found 15.3±10.3 μg/L. The 25(OH) vitamin D levels of 91% (780) patients were below normal limits. In 44.2% (379) of the patients, 25(OH) D level was <10 μg/L and severe deficiency were found. Vitamin D levels were lower in females than those in males. Secondary hyperparathyroidism was detected in 17% (146) of the patients. Conclusion: Vitamin D deficiency, which is still an important world-wide medical problem despite all preventive measures, is commonly seen in our country and affects especially female population.